Predicting Factors of Pain and Pain Management Behaviors in Working-age Patients undergoing Major Abdominal Surgery - Sriwichai, Premrudee; Sajai, Kanjana; Saklaw, Jeeranan (Journal of The Royal Thai Army Nurses, 2023)
The objective of this study was to study predicting factors of pain and pain management behaviors of working-age patients undergoing major abdominal surgery. The sample consisted of 100 patients who underwent major abdominal surgery. Data were collected by using personal data record form, pain questionnaire, Disturbance Perception Questionnaire Pain severity perception questionnaire, Pain Management Questionnaire, and Patient Expectation Questionnaire for pain management. Data were analyzed by using descriptive statistics, Pearson’s correlation, and predicting factors using Stepwise Multiple Regression. The study results showed that perceived disturbances and pain management had a low positive correlation with pain in working-age patients undergoing major abdominal surgery (r = .22 p<.05; r = .21 p<.05, respectively). Pain severity had a moderate positive correlation with pain (r = .66, p<.05). The type of surgery had a low negative correlation with pain (r = .24, p<.05). The severity of pain and type of surgery predict the pain of patients who have undergone major abdominal surgery accounted for 41.80%. Recommendations: Nurses should pay attention to evaluate the severity of pain and encourage patients to understand self-pain management to effectively reduce pain.